Importance of pharmacist in pharmacotherapeutic adhesion of patients with HIV/AIDS (Research, Society and Development, 2020)
Acquired Immunodeficiency Syndrome (AIDS) is a disease characterized by progressive stages after the vulnerability of the immune system to the Human Immunodeficiency Virus (HIV) infection, which can affect the worldwide population. The antiretroviral therapy (ART) indicated for infected patients improves the patient's quality of life by preventing disease progression. The health team, including the pharmacist, is essential to assist and ensure the safety and efficacy of pharmacotherapeutic treatment. This work aims to present the importance of pharmaceutical care in pharmacotherapeutic follow-up for HIV/AIDS patients through an integrative literature review. 14 articles were analyzed, which showed a prevalence of the disease in a male patient over 30 years old, with an incidence always greater than 50%. The main causes that hinder adherence to antiretrovirals are disinformation on the risk of non-adherence, lack of understanding about prescription drugs, low education, drug, and alcohol use among male patients. Studies have shown that pharmaceutical care and the multidisciplinary team can positively assist in increasing adherence to antiretrovirals. Therefore, the interventions and guidelines carried out by the pharmaceutical professional together with the health team show promising results that favor adherence to medications by patients with HIV/AIDS. However, greater commitment and collaboration between health professionals is necessary to improve the quality of life of these patients, working mainly in the process of adhering to treatment.